2017
DOI: 10.1186/s13045-017-0530-z
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of the ephrin receptor kinase signalling by GLPG1790 in vitro and in vivo reverts oncophenotype, induces myogenic differentiation and radiosensitizes embryonal rhabdomyosarcoma cells

Abstract: Background: EPH (erythropoietin-producing hepatocellular) receptors are clinically relevant targets in several malignancies. This report describes the effects of GLPG1790, a new potent pan-EPH inhibitor, in human embryonal rhabdomyosarcoma (ERMS) cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…Interestingly, the Ephs are among the few receptor tyrosine kinases known to negatively regulate RAS signaling and its downstream pathways in a variety of cell types [39] though, under some circumstances, Eph receptors activate, rather than inhibit MAPK signaling [40]. We also have shown in previous reports that GLPG1790 induces irreversible growth arrest and differentiation by downregulating ERK in RMS cells [11]. Herein, GLPG1790 strongly and persistently increased the phosphorylation/ activation of ERK signaling in HCT116 cells indicating that relationship between RAS and Eph signaling is similar to that of RMS cells.…”
Section: Journal Of Oncologymentioning
confidence: 58%
See 3 more Smart Citations
“…Interestingly, the Ephs are among the few receptor tyrosine kinases known to negatively regulate RAS signaling and its downstream pathways in a variety of cell types [39] though, under some circumstances, Eph receptors activate, rather than inhibit MAPK signaling [40]. We also have shown in previous reports that GLPG1790 induces irreversible growth arrest and differentiation by downregulating ERK in RMS cells [11]. Herein, GLPG1790 strongly and persistently increased the phosphorylation/ activation of ERK signaling in HCT116 cells indicating that relationship between RAS and Eph signaling is similar to that of RMS cells.…”
Section: Journal Of Oncologymentioning
confidence: 58%
“…Unexpectedly, GLPG1790 enhanced expression of cyclin D1, known to be a positive regulator of the G 1 /S cell-cycle transition [28]. We have recently shown that GLPG1790 upregulates the expression of cyclin D1 in RMS, inducing the cytoplasmatic/perinuclear accumulation of the protein [11]. Reports have shown that this accumulation correlates with a lower proliferative index in several cancer types [29,30].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Target genes were analyzed by quantitative real-time PCR (qPCR), by using the following primers from Qiagen: SOD-2 (QT01008693), CAT (QT00079674), GPx4 (QT00067165), NRF2 (QT00027384) and β-Actin (ACTB) (QT00095431). Each sample was run in triplicate, in at least two independent experiments, on a StepOne Real Time System (Applied Biosystems) machine [15]. Relative quantification (RQ) of each mRNA in RR samples in comparison to PR-cells was calculated by the comparative Ct method (2 -ΔΔCt ), using the StepOne v2.3 software (Applied Biosystems).…”
Section: Rna Isolation and Quantitative Real-time Pcrmentioning
confidence: 99%